Intentional Listening: Practicing a Vital Inclusive Behavior (Global Journal of Human-Social Science, 2023)
In a classroom setting intentional listening has six distinctive stages Actively inviting classmates thoughts and opinions reflectively considering every aspect of what others say thanking others for expressing their ideas and beliefs putting what one has heard in a broader societal context connecting peers with similar ideas and insights and identifying the point of intersection between what you have heard and your own intuitions and experiences In instructional environments intentional listening takes practice
Keywords: listening; dialogue; inclusion; reflection; social-impact teaching